Statistics anxiety, state anxiety during an examination, and academic achievement. (24th September 2012) - Macher, Daniel; Paechter, Manuela; Papousek, Ilona; Ruggeri, Kai; Freudenthaler, H.Harald; Arendasy, Martin
Abstract : Background: A large proportion of students identify statistics courses as the most anxiety‐inducing courses in their curriculum. Many students feel impaired by feelings of state anxiety in the examination and therefore probably show lower achievements. Aims: The study investigates how statistics anxiety, attitudes (e.g., interest, mathematical self‐concept) and trait anxiety, as a general disposition to anxiety, influence experiences of anxiety as well as achievement in an examination. Sample: Participants were 284 undergraduate psychology students, 225 females and 59 males. Methods: Two weeks prior to the examination, participants completed a demographic questionnaire and measures of the STARS, the STAI, self‐concept in mathematics, and interest in statistics. At the beginning of the statistics examination, students assessed their present state anxiety by the KUSTA scale. After 25 min, all examination participants gave another assessment of their anxiety at that moment. Students' examination scores were recorded. Structural equation modelling techniques were used to test relationships between the variables in a multivariate context. Results: Statistics anxiety was the only variable related to state anxiety in the examination. Via state anxiety experienced before and during the examination, statistics anxiety had a negative influence on achievement. However, statistics anxiety also had a direct positive influence on achievement. This result may be explained by students' motivational goals in the specific educational setting. Conclusions: The results provide insight into the relationship between students' attitudes, dispositions, experiences of anxiety in the examination, and academic achievement, and give recommendations to instructors on how to support students prior to and in the examination.